Development of Animation Video on How to Make Adult Women's Clothing Patterns in Sewing Program at Samir Course and Training Institute of Palembang City - Meryanti, Meryanti; Shomedran, Shomedran; Sapitri, Erna Retna (Journal of English Language and Education, 2025)
Sewing skills training is a part of non-formal education aimed at improving participant’s abilities in fashion design. One essential topic in this training is pattern making, which serves as the foundation for the sewing process. However, many participants still struggle to understand the proper steps in creating clothing patterns. This study aims to develop an animated video as a learning medium on how to create patterns for adult women’s clothing at LKP Samir in Palembang city. The research method used is research and development (RD) with the ADDIE model, conducted up to the implementation stage, which includes Analysis, Design, Development, and implementation. The research subjects were sewing gcourse participants at LKP Samir. Data collection instruments included expert validation questionnaires on contetnt, media, and language, as well as response questionnaires for learners. The results showed that the developed animated video was deemed highly feasible and received positive responses as it helped learners better understand the steps in pattern making.